2021
DOI: 10.3390/su13042104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an 8-Week Yoga-Based Physical Exercise Intervention on Teachers’ Burnout

Abstract: The purpose of this quasi-experimental study was to investigate the efficacy of an 8-week yoga-based physical exercise program to improve mental and emotional well-being and consequently reduce burnout among teachers. We considered yoga because it is a discipline that enhances body awareness and encourages the contact with nature and the respect for every form of life, with a view to a more sustainable and greener global system. We recruited 40 professional educators (40–47 years), teachers in a public high sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 59 publications
1
9
0
2
Order By: Relevance
“…Noteworthy, all of those studies demonstrated positive alterations in selected psychological-health-related markers among overweight and obese adults [ 73 , 74 , 75 , 78 , 80 , 81 , 87 , 88 , 93 ]. These findings are in agreement with those reported for other populations, supporting the beneficial role of yoga practice in lowering anxiety, depression, stress [ 129 ], and professional burnout [ 130 ]. In general, the improvements in well-being through lower anxiety and depression levels have been considered as an important research area.…”
Section: Discussionsupporting
confidence: 92%
“…Noteworthy, all of those studies demonstrated positive alterations in selected psychological-health-related markers among overweight and obese adults [ 73 , 74 , 75 , 78 , 80 , 81 , 87 , 88 , 93 ]. These findings are in agreement with those reported for other populations, supporting the beneficial role of yoga practice in lowering anxiety, depression, stress [ 129 ], and professional burnout [ 130 ]. In general, the improvements in well-being through lower anxiety and depression levels have been considered as an important research area.…”
Section: Discussionsupporting
confidence: 92%
“…This suggested that when PHNs experience high emotional labor, increasing PHS and strengthening POS could help alleviate burnout. Interventions that provide effective emotional regulation management education, communication, and psychological counseling support [ 43 ] to positively manage the negative effects of emotional labor and maintain fitness and health by recommending meditation, yoga, or exercise [ 44 ] could help reduce or prevent PHNs’ burnout. Moreover, managers and organizations where the PHNs belong should analyze the COVID-19-related burden, role change, and work scope to provide organizational support, such as adequate rest, flexible work hours, work allocation, and appropriate personnel management, to alleviate burnout [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A ausência de diferenças significativas numa maior quantidade de variáveis em estudo pode ser compreendida pelo reduzido número de sessões, bem como pelos constrangimentos associados às mesmas (nomeadamente o número de sessões teórico-práticas realizadas em regime online). Este resultado parece indicar que esta duração/frequência do programa apesar de poder ser suficiente para ter algum efeito em algumas variáveis, não o será noutros domínios, algo que foi também referido em outros programas semelhantes (ex., Latino et al, 2021). Assim, e com vista a procurar um melhor entendimento do efeito que Projeto "RespirArFundo" 199 este programa teve, foi adotada uma metodologia qualitativa complementar (grupo focal).…”
Section: Discussionunclassified